Influência da Espessura nas Propriedades Mecânicas de Compósitos Híbridos Interlaminares de Curauá/Vidro/Poliéster - Angrizani, Clarissa C.; Amico, Sandro C.; Cioffi, Ma Odila H. [UNESP]; Zattera, Ademir J. (Assoc Brasil Polimeros, 2014)
The interest in the use of vegetable fibers (e.g. jute, sisal and curaua) for more noble applications, such as reinforcement in polymeric composite materials, has increased over the years due to a variety of aspects, especially those related to environmental legislation and community awareness regarding the life cycle of products. In this context, the aim of this work is to develop hybrid interlaminate curaua/glass/insaturated polyester composites by hot compression molding and to analyze their mechanical properties as a function of the thickness of the laminate. The short beam strength of the thickest sample decreased due to its higher void content. Furthermore, the thinnest sample showed lower hardness, and lower impact, tensile and Iosipescu shear strength, partly attributed to its lower fiber volumetric fraction. Thus, in general, the most adequate laminate was the one comprising eight layers, four of which were of glass fiber and four of curaua fiber, but only if flexural loading is not critical.
Influence of Thickness on the Mechanical Properties of Hybrid Interlaminate of Curaua/Glass/Polyester Composites
Keywords: Laminate; hybrid; vegetal fiber; curaua